2020
DOI: 10.1007/s42452-020-2889-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and dielectric studies of poly(1-naphthylamine)–tungsten disulphide nanocomposites

Abstract: Here, novel poly(1-naphthylamine)-tungsten disulphide (PNA-WS 2 ) nanocomposites were synthesized through an in-situ chemical oxidative polymerization of 1-naphthylamine in the presence of ultrasonically dispersed WS 2 . The effect of WS 2 addition on the optoelectrical, morphological and thermal properties of PNA was studied by using different analytical tools. SEM images revealed that PNA aggregates are well supported on the dispersed WS 2 sheets. The formation of a fibrous network of PNA over the dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Also, the remaining weight loss at about 380-450 • C is ascribed to the carbonization of the grafted polymeric branches onto the WS 2 nano-sheets. [33][34][35] The data obtained from TGA pattern confirmed that the surface modification of the WS 2 nano-sheets has been accomplished.…”
Section: Characterization Of Mnasupporting
confidence: 56%
See 1 more Smart Citation
“…Also, the remaining weight loss at about 380-450 • C is ascribed to the carbonization of the grafted polymeric branches onto the WS 2 nano-sheets. [33][34][35] The data obtained from TGA pattern confirmed that the surface modification of the WS 2 nano-sheets has been accomplished.…”
Section: Characterization Of Mnasupporting
confidence: 56%
“…The findings were similar to the other reports. [32,33] Based on the MNA thermogram, three steps of the weight loss were detected for the synthesized MNA. The first weight loss at about 80-100 • C is ascribed to the evaporation of the adsorbed water from WS 2 particles.…”
Section: Characterization Of Mnamentioning
confidence: 99%
“…The observed UV-Vis spectrum exhibited wide absorbance peaks in the visible range centered at ~510 nm. The presence of a well-defined peak at 510 nm in the UV-Vis absorption spectrum was due the polaronic n−π * transitions [21,40,43]. Figure 4b shows a typical Tauc's plot for the as-synthesized PNA nanoparticles.…”
Section: Uv-visible Analysismentioning
confidence: 98%
“…This further affirms the improved energy storage capacity of PANI-TiO 2 -PPy electrode. Figure 12b displays the charge-discharge curves of PANI-TiO 2 -PPy electrode at different current densities (6,8,10,12, and 14 A g À1 ). The GCD curves of fabricated ternary electrode exhibits an asymmetrical shape over the range of current densities that confirm the pseudocapacitive charge storage mechanism.…”
Section: Galvanostatic Charge/discharge (Gcd) Measurementsmentioning
confidence: 99%
“…More recently, researchers are focusing on various combinations of pseudocapacitive materials (conducting polymers and transition metal oxides) to ensure their possible use as efficient electrode materials that can drastically improve the device's energy density along with power density. 5 Many conducting polymer based active electrode materials, namely polyaniline (PANI), 6 polythiophene (PTh), 7 polypyrrole (PPy), 8 polyindole (PIN), 9 poly(o-phenylenediamine) (PoPD), 10 poly(naphthylamine) (PNA), 11 polycarbazole (PCz), 12 polyanisidine (PANIS), 13 poly (3,4-ethylenedioxythiophene) (PEDOT), 14 poly(para-phenylene) (PPP), 15 poly(phenylenevinylene) (PPV), 16 polyfuran (PF), 17 poly(acetylene) (PAC), 18 poly(p-phenylene sulfide) (PPS), 19 and poly(p-phenylene vinylene) (PPV) 20 have been explored in the past. Among the mentioned conducting polymers, PANI and PPy based electrode materials have received much attention in high-performance supercapacitors as they possess distinctive characteristics such as good intrinsic conductivity, increased electrochemical activity and high energy density.…”
Section: Introductionmentioning
confidence: 99%